ORIGINAL ARTICLE: Efficacy of C1-C2 Sustained Natural Apophyseal Glide (SNAG) Versus Posterior Anterior Vertebral Mobilization (PAVMs) in the Management of Cervicogenic Headache - Muhammad Khan; Syed Shahzad Ali; Rabail Rani Soomro (Journal of Basic & Applied Sciences, 2014)
Objectives: To determine the effect of a C1-C2 sustained natural apophyseal glide (SNAG) as compare to posterior anterior (PA) vertebral mobilization on cervicogenic headache. Study Design: Randomized Control Trial. Method: The study was conducted on 60 patients with CGH. In this study, patients were divided into two groups, group A and group B equally. Group A of 30 patients received SNAG and at the same time Group B of 30 patients were treated with PAVMs. A pre tested and structured questionnaire was used to collect data. Data was entered and analyzed by using SPSS 19. Outcome Measures: Pain and disability was measured on Visual Analog Scale (VAS) (0-10) and Neck Disability Index (NDI) before and after the treatment. Results: The study showed significant results for both the interventions in the treatment of CGH but SNAG mobilization has been more effective in reducing pain in CGH patients. Conclusions: On the basis of this study, it is proved that cervical SNAGS is more effective for the treatment of cervicegenic headaches as compared to PAVMs.